2015
DOI: 10.1002/cpp.1982
|View full text |Cite
|
Sign up to set email alerts
|

Anxious Children and Adolescents Non‐responding to CBT: Clinical Predictors and Families' Experiences of Therapy

Abstract: Youths with an anxiety disorder, who had a primary social phobia diagnosis and those, who had a comorbid mood disorder, were more likely not to respond to manualized group CBT. Parents of those non-responding youths often considered them as motivated to overcome their difficulties, but due to their symptomatology, they were unreceptive, reluctant and ambivalent and therefore not actively involved in therapy. The non-responding youths with social phobia felt evaluated and nervous of what others thought of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…However, a number of studies have shown that outcomes from generic CBT are less good for young people with SAD compared to those with other anxiety disorders. Young people (mixed child and adolescent samples) with SAD are significantly less likely to lose their diagnosis of SAD after treatment compared with young people with other anxiety diagnoses (Crawley et al 2008 ; Ginsburg et al 2011 ; Hudson et al 2015a , b ; Lundkvist-Houndoumadi and Thastum 2017 ; Kodal et al 2018 ).…”
Section: Current Treatments For Social Anxiety Disorder In Adolescentmentioning
confidence: 99%
“…However, a number of studies have shown that outcomes from generic CBT are less good for young people with SAD compared to those with other anxiety disorders. Young people (mixed child and adolescent samples) with SAD are significantly less likely to lose their diagnosis of SAD after treatment compared with young people with other anxiety diagnoses (Crawley et al 2008 ; Ginsburg et al 2011 ; Hudson et al 2015a , b ; Lundkvist-Houndoumadi and Thastum 2017 ; Kodal et al 2018 ).…”
Section: Current Treatments For Social Anxiety Disorder In Adolescentmentioning
confidence: 99%
“…Cooccurring problems in youth are associated with academic problems, relationship difficulties, and higher rates of suicide attempts and completions (Cummings et al 2014). Youth with co-occurring problems also have greater severity of disorders, poorer prognoses, increased treatment challenges, and greater unmet needs for treatment compared to individuals with either type of disorder alone (Cummings et al 2014;Lundkvist-Houndoumadi and Thastum 2017;Urbanoski et al, 2007). Nevertheless, very little is known about this group with respect to the nature of the care these youth receive.…”
Section: Introductionmentioning
confidence: 99%
“…Generic CBT programs for children and adolescents struggling with anxiety disorders have shown substantial effects for other anxiety disorders [5, 46]. However, recent studies indicate that adolescents with SAD have poorer outcomes following generic treatment compared to adolescents struggling with other anxiety disorders like generalized anxiety, separation anxiety, specific phobia, or obsessive compulsive disorder [26, 31, 33, 46].…”
Section: Introductionmentioning
confidence: 99%